The Effect Of Capital Adequacy Ratio And Loan To Deposit Ratio On Stock Prices Study Of Banking Companies Listed On The Indonesia Stock Exchange (IDX) In 2020–2024 - A. Nur Azilah; Anwar Ramli; Nurul Fadilah Aswar; Nurman; Annisa Paramaswary (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The capital market has an important role in supporting economic activities by providing long-term funding sources for companies as well as an investment vehicle for the public. The development of the banking sector in Indonesia shows that financial performance often influences stock price movements, although the results are not always consistent between companies. This problem encourages this study which aims to analyze the effect of the Capital Adequacy Ratio (CAR) and the Loan to Deposit Ratio (LDR) on stock prices in banking companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study uses a quantitative approach with a multiple linear regression method through the assistance of the SPSS application, while the sample is determined by a purposive sampling technique in 16 banking companies over 5 years of observation, resulting in 80 observations. The results of the study show that CAR has a significant negative effect on stock prices (t = -2.482 sig = 0.015), while LDR has a significant negative effect on stock prices (t = -2.846 sig = 0.006). The coefficient of determination (R²) value is 0.162, which means that 16.2% of the variation in stock prices can be explained by CAR and LDR, while the remaining 83.8% is explained by other factors outside the model. This study supports the Signaling Theory which states that financial performance information can provide signals to investors in making investment decisions. This finding confirms that the bank's ability to maintain capital adequacy provides a positive signal to investors, while liquidity management through LDR has not been fully considered as the main factor determining stock prices.